From action to transaction: some implications of pragmatism and its concept of agency for development research and practice - Pablo Garcés-Velástegui (Revista Iberoamericana de Estudios de Desarrollo)
Development suggests the notion of «good change» and its research and practice are about bringing it to fruition. Perhaps, because of this emphasis on application, relatively less attention has been given to philosophical issues, although shedding more light on the latter can contribute to the former. Positivism and, to a lesser extent, constructivism, with their advantages and disadvantages, have dominated the field. Against this conventional dichotomy, this article argues in favour of philosophical classic pragmatism as an alternative and does so employing philosophical ontology. From this perspective, pragmatism adheres to mind-world monism and phenomenalism. As such, it demands healthy awareness and criticism of preferences and biases, whether personal or contextual, in the self and in the subjects of interest. It entails a call for plurality, to harness practical reason to solve practical problems, turning indeterminate situations into determinate ones, thereby generating warranted assertions.